ARTIFICIAL INTELLIGENCE AS A PERSONALIZED TUTOR IN LANGUAGE LEARNING: A SYSTEMATIC REVIEW - Sangkala, Ismail; Mardonovna, Nargiza Sulaymanova (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This systematic review comprehensively examines the application of artificial intelligence (AI) in personalized language learning. By analyzing existing research, the study aims to evaluate the effectiveness, challenges, and potential of AI-powered tutoring systems. Findings indicate that AI offers significant benefits, including tailored instruction, increased engagement, and improved accessibility. However, the review also highlights concerns such as data privacy, algorithm bias, and the need for human interaction. Overall, AI presents promising opportunities for enhancing language education, but careful consideration of ethical implications and technological limitations is essential for its successful implementation.